Investigation of toughness of ultra high performance fibre reinforced concrete (UHPFRC) beam under impact loading. (January 2017) - Mao, L.; Barnett, S.J.
Highlights: The paper provides a systematic study of the toughness of UHPFRC beam at various strain rates. Field tests show variation of toughness of UHPFRC beam with various fibre volumes. Performance of UHPFRC beam under impact loading can be simulated with good quality using numerical model. Numerical model can provide toughness variation of UHPFRC beam without the influence due to random fibre orientation and distribution. Abstract: This paper provides a systematic study about toughness of ultra high performance fibre reinforced concrete (UHPFRC) in order to better understand the UHPFRC resistance under impact loading condition. UHPFRC beams containing various fibre volumes are tested under impact load at different strain rate. From the test results, the relationship between UHPFRC toughness and strain rate can be determined. Moreover, a numerical model of UHPFRC beam under impact load is developed and its performance is verified using test data. With developed UHPFRC model, the evolution of UHPFRC toughness can be better investigated.